A minimally invasive cerclage of the tibia in a modified Goetze technique: operative technique and first clinical results - Förch, Stefan; Reuter, Jan; von der Helm, Franziska; Lisitano, Leonard; Hartwig, Christopher; Sandriesser, Sabrina; Nuber, Stefan; Mayr, Edgar (European journal of trauma and emergency surgery (Munich : 2007), 2022)
Introduction In spiral fractures of the tibia, the stability of an osteosynthesis may be significantly increased by additive cerclages and, according to biomechanical studies, be brought into a state that allows immediate full weight bearing. As early as 1933, Goetze described a minimally invasive technique for classic steel cerclages. This technique was modified, so that it can be used for modern cable cerclages in a soft part saving way. Method After closed reduction, an 8 Fr redon drain is first inserted in a minimally invasive manner, strictly along the bone and placed around the tibia via 1 cm incisions on the anterolateral and dorsomedial tibial edges using a curette and a tissue protection sleeve. Via this drain, a 1.7 mm cable cerclage can be inserted. The fracture is then anatomically reduced while simultaneously tightening the cerclage. Subsequently, a nail or a minimally invasive plate osteosynthesis is executed using the standard technique. Using the hospital documentation system, data of patients that were treated with additional cerclages for tibial fractures between 01/01/2014 and 06/30/2020 were subjected to a retrospective analysis for postoperative complications (wound-healing problems, infections and neurovascular injury). Inclusion criteria were: operatively treated tibial fractures, at least one minimally invasive additive cerclage, and age of 18 years or older. Exclusion criteria were: periprosthetic or pathological fractures and the primary need of reconstructive plastic surgery. SPSS was used for statistical analysis. Results 96 tibial shaft spiral fractures were treated with a total of 113 additive cerclages. The foregoing resulted in 10 (10.4%) postoperative wound infections, 7 of which did not involve the cerclage. One lesion of the profundal peroneal nerve was detected, which largely declined after cerclage removal. In 3 cases, local irritation from the cerclage occurred and required removal of material. Conclusion In the described technique, cerclages may be inserted additively at the tibia in a minimally invasive manner and with a few complications, thus significantly increasing the stability of an osteosynthesis. How this ultimately affects fracture healing is the subject of an ongoing study.